The effect of service quality on customer satisfaction at government service agency: road transport department - Md Nor, Mohamad Niza; Mohd Razali, Mohd Fazly; Ismail, Mohammad (2011)
The purpose of this research paper is to examine the effect of service quality on customer satisfaction among a group of customer towards a public sector organization at Road Transport Department, Alor Setar, Kedah. The important of this research is to identify level of customer's satisfaction toward the services provided by Road Transport Department, in order to improve their customer satisfaction and service performance. This study is cross-sectional and descriptive in nature. Service quality consists of service product, service delivery and service environment. In order to obtain data for this study, questionnaires were administered to a total of 331 customers of the agency however 249 sets of questionnaires that were answered by the respondents, who are customers of particular public department. The finding and hypothesis were analyzed by using Statistical Program for Science (SPSS). Customers' satisfaction was examine through 3 major independence variable consist of service product, service delivery and service environment. Data gathered through this analysis being analyzed and illustrated in the form of tables and bar charts. The model in this study is significant and can be assumes to be able to predict on service quality as determinant of customer satisfaction at this department. The hypotheses were tested using multiple regressions. The findings indicate that service product significantly and positively related to customer satisfaction. However, service delivery and service environment were not significant predictors of satisfaction. This study expanded the service encounter literatures by offering evidence in the context of public sector. Customers' satisfaction will be enhanced if they perceive that there is a favourable service product. Relationship quality has a significant influence on behavioural intentions. That means customers' satisfaction and trust established will improve positive word-of-mouth and repeated patronage. Implication and recommendation are discussed in this study to provide some understanding and guidelines which could help the department for several appropriate actions in satisfying their customers' need and wants. A continuous improvement by the Road Transport Department is essential towards achieving the public or society needs and its organizational goals and objectives.